EVALUASI STATUS KESUBURAN TANAH PADA TANAMAN PADI DI KECAMATAN SOA KABUPATEN NGADA - Hurynt, Maria Ivandi Sombo; Wangge, Emilia Simplisiu Ake; Tensiana Tima, Maria (Agriculture Faculty of Flores University, 2025)
Rice productivity is greatly influenced by the level of soil fertility, which is the main source of nutrients. Rice fields in Soa District, Ngada Regency, consist of irrigated and rain-fed rice fields managed differently. Excessive use of chemical fertilizers without the addition of organic matter is feared to reduce soil quality, so a study is needed to determine the status of soil fertility in both types of land. The study was conducted through a field survey with soil sampling at six locations, three each in irrigated rice fields and three in rain-fed rice fields. At each location, five sample points were taken using the diagonal method at a depth of 0–20 cm. Samples were analyzed at the Soil Chemistry Laboratory of Nusa Cendana University to determine pH, Organic Carbon, Total Nitrogen, Available Phosphate, Available Potassium, Cation Exchange Capacity (CEC), and Base Saturation (BCC). The analyzed data were then evaluated using the matching method and t-test to see differences between land types. The analysis results showed that the irrigated land is classified as fertile to very fertile with high P and K content, very high CEC and BCC values, and medium Organic Carbon. In contrast, rainfed land showed varying fertility levels from low to high, with the main constraints being low organic carbon, phosphorus, and potassium. The t-test showed no statistically significant differences, but agronomically, the differences between locations were quite clear. This study emphasizes the importance of adding organic matter and implementing balanced fertilization, especially in rainfed land, to maintain nutrient availability and support sustainable rice production.